A novel algorithm for collaborative behavior of multi-robot in autonomous reconnaissance - Khan, Md. Raisuddin; Billah, Md. Masum; Ahmed, Mohiuddin; Abdul Aziz, Normaziah (2011)
Robots in a group can solve problems in fundamentally different ways than individuals while achieving higher levels of performance, however, programming and coordination of a group of robots poses big challenge. This paper addresses the problem of mobile robots executing complex group behaviors in an attempt to form collaborative group behavior of hexapod robots in reconnaissance mission. A set of basic sharing behaviors for a group of hexapod robots is first assigned. These behaviors then evolve into more complicated group behaviors such as flocking using collaboration and indirect communication. This is then used to solve specific problems relating to goal finding and obstacle avoidance within a real world environment. The sharing behavior is designed with a stable navigation towards practical applications, such as reconnaissance mission and coordinated motion. All algorithms have been developed and tested on two hexapod robots.